PENGARUH DIVIDEN, UTANG, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PROPERTY DI BURSA EFEK INDONESIA (BEI) - utama, I Made Dharma Putra; Dana, I Made (E-Jurnal Manajemen, 2019)
Financial report analysis is conducted to determine the health level of the company. The property and real estate sector is one of the most important sectors in a country. This can be used as an indicator to analyze the economic health of a country. The property and real estate industry is one sector that signals a fall or the development of a country's economy. This indicates that more and more companies engaged in the property and real estate sector indicate the growing economy in Indonesia. This study aims to determine the effect of dividends, debt, and profitability on firm value on Property Companies on the Indonesia Stock Exchange in 2012-2016. Based the results of the analysis that has been done, the results obtained are dividend policy represented by the House of Representatives, the debt policy represented by DER, profitability represented by ROE, get a significant positive result on firm value.      Keyword : DPR, DER, ROE, firm value